Christian Attitude Towards Religious Plurality in Indonesia - Baginda Sitompul; Sudarman Lubis; Lamria H. Lumbanbatu; Evanni Sihombing; Melda A. Simarmata (International Journal of Christian Education and Philosophical Inquiry, 2024)
Pluralism refers to the attitude that although every religion has a different style, method or path, it leads to the same goal, namely God, so one of the goals of Pluralism is to build tolerance. This research is intended to provide an understanding that in our existence as a pluralist society we must respect and respect each other in order to create religious harmony and moderation. Diversity is certainly beautiful, but it is not impossible that in diversity there will be conflicts based on differences, so the understanding of pluralism emerges to make the nation aware that even though we are different in ideology, belief and culture, we are still both human and equally one nation, so that among we create a feeling of mutual appreciation and mutual respect, not tearing each other down. The author uses a descriptive qualitative research method with a literature study approach to see how Christianity is amidst Plurality. The Bible teaches that Christians must abstain from fleshly desires, and as servants of God must have a way of life that is good and right before God. The Christian attitude towards pluralism should emulate Jesus' attitude towards pluralism, namely respecting every difference by building mission and dialogue according to the context faced. Christians must be inclusive and open to diversity but remain strong and firm in their own faith.